Relación entre la presencia de intolerancia a la lactosa y los niveles séricos de inmunoglobulina a en niños menores de dos años que acuden al Centro de Salud N° 1 de Loja. - Alvarado Jaramillo, Daniela Johanna (2018)
The Lactose intolerance is caused by the imbalance between the amount of lactose ingested and the ability of lactase to hydrolyse the disaccharide, this alteration occurs frequently, constituting a health problem that is increasing, 50% of the world population suffers from this digestive disorder and may vary from one population to another, the symptoms depend on the amount of lactose ingested, and the degree of intolerance, presenting the first manifestations during the first years of life, more frequently in the younger infant. The present study entitled "Relationship between the presence of lactose intolerance and serum levels of Immunoglobulin A in children under two years of age who attend Loja Health Center No. 1", had as its general objective to establish the relationship between the presence of Lactose intolerance and serum immunoglobulin A levels in children younger than 2 years who had diarrhea. The study was of a descriptive type, and the cross section included a sample of 95 patients, who met the inclusion criteria, from November 2016 to January 2017; the determination of reducing sugars was carried out by the Fehling method, obtaining as a result that 33% of the patients presented lactose intolerance, and 61% of these by determination with the Immunoturbidimetric method presented low serum levels of IgA, finding themselves directly related to the presence of lactose intolerance. Finally, the results obtained were disseminated to the health personnel and parents of the children participating in the study. Key Words: lactose intolerance, Immunoglobulin A.